The expansion of a Simex estimator in the nonlinear errors-in-variables model with small measurement errors - Gontar, O.; Kuchenhoff, H. (Інститут математики НАН України, 2008)
The nonlinear structural errors-in-variables model is investigated. We consider a Simex estimator with polynomial extrapolation function. The expansion of a Simex estimator is based on the asymptotic expansion of a naive estimator for small measurement errors. It is shown that the Simex estimator has an asymptotic deviation from a true value of the unknown parameter which is negligible compared with a measurement error variance, while the deviation of the naive estimator is proportional to the measurement error variance.